Pengaruh Kepemimpinan Dosen, Kualitas Layanan Akademik, dan Kualitas Layanan Administratif Terhadap Tingkat Kepuasan Mahasiswa - Mochamad Enoh (Universitas Negeri Malang, 2016)
This study aims to investigate the effect of lecturers leadership behavior in the teaching learning process, the academic service quality on students' satisfaction. Questionaires were distributed to 327 students, who had been proportionally and randomly sampled. The results of discriptive and regression analyses indicate that lecturers' leadership, academic-service quality mostly fall in the category ranging from good to fair quality, and that there was a significant effect of those three variables on students' satisfaction.